Signaling Sustainability Leadership: Empirical Evidence of the Value of DJSI Membership - Robinson, Michael 1958-; Kleffner, Anne E.; Bertels, Stephanie (2011)
We explore the relationship between corporate sustainability, reputation, and firm value by asking whether signaling sustainability leadership through membership on a recognized sustainability index is value generating. Increasingly, stakeholders are demanding that firms demonstrate their commitment to sustainability. One signal that companies can send to stakeholders to indicate that they are sustainability leaders is membership on a recognized “best in class” sustainability index. This article explores both the short-term and the intermediary impact on North American firms of being included or removed from the Dow Jones Sustainability World Index (DJSI). Our results provide evidence that being added to the DJSI results in a sustained increase in a firm’s share price, suggesting that the benefits of being included on the DJSI outweigh the costs associated with applying. This article also notes a temporary decrease in the value of firms for the first 10 days after their removal from the DJSI; however, this effect is eliminated within the next ten trading days.
Keywords: Sustainability leadership; Sustainability; Reputation; Financial Performance; Dow Jones Sustainability Index (DJSI); Corporate social responsibility (CSR)